2021
DOI: 10.1002/pssa.202100452
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Crystalline AlN Passivation for Reduced RF Dispersion in Strained‐Channel AlN/GaN/AlN High‐Electron‐Mobility Transistors

Abstract: The recent demonstration of ≈ 2  W mm−1 output power at 94 GHz in AlN/GaN/AlN high‐electron‐mobility transistors (HEMTs) has established AlN as a promising platform for millimeter‐wave electronics. The current state‐of‐art AlN HEMTs using ex situ‐deposited silicon nitride (SiN) passivation layers suffer from soft gain compression due to trapping of carriers by surface states. Reducing surface state dispersion in these devices is thus desired to access higher output powers. Herein, a potential solution using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…By increasing the maximum drain current, we confirmed that the drain current with bias stress was also significantly increased compared to the HEMT in [8]. Reduction in drain current was evaluated between the two devices by dividing I d with bias stress by I d without stress at drain voltage of 5V [5], [10]. For the bias stress of V gs =−5 V and V ds =0 V, 6% and 10% drain current reduction was observed for the HEMT in this study and the HEMT in [8], respectively.…”
Section: Resultsmentioning
confidence: 55%
“…By increasing the maximum drain current, we confirmed that the drain current with bias stress was also significantly increased compared to the HEMT in [8]. Reduction in drain current was evaluated between the two devices by dividing I d with bias stress by I d without stress at drain voltage of 5V [5], [10]. For the bias stress of V gs =−5 V and V ds =0 V, 6% and 10% drain current reduction was observed for the HEMT in this study and the HEMT in [8], respectively.…”
Section: Resultsmentioning
confidence: 55%
“…Long‐term efforts aim at in situ passivation of the AlN/GaN/AlN heterostructure. [ 23 ] Potential MBE‐grown passivation materials include crystalline and amorphous AlN, as well as SiN.…”
Section: Results and Remarksmentioning
confidence: 99%
“…Partial relaxation of the AlN barrier layer is expected due to 0.6% strain in the 200 nm GaN channel. [ 23 ] Transport characteristics were measured via Hall effect at room temperature, showing a mobility of 586 cm2 V1 s and sheet concentration of 3.2 × 1013 cm2. The HEMT processing started with regrown ohmic contacts.…”
Section: Device Fabricationmentioning
confidence: 99%
“…The presence of intrinsic polarization [1] in III-nitride semiconductors have been used to generate high mobility 2D electron gases (2DEGs) by utilizing the positive polarization discontinuity across a heterointerface since the early 1990s. These have yielded as-grown 2DEG densities [2,3] ranging from low-5 × 10 12 to high 5 × 10 13 cm −2 without the need of donor dopants. These 2DEGs have a high room temperature mobility of 1400-1800 cm 2 V −1 s −1 resulting in low sheet resistances <200 Ω per sq.…”
Section: Introductionmentioning
confidence: 99%